PENGARUH ETOS KERJA DAN DISIPLIN KERJA TERHADAP KOMITMEN ORGANISASI PEGAWAI PADA DINAS SOSIAL KABUPATEN PEGUNUNGAN ARFAK - Toni Toansiba; Yohanes Damaskus Resi; Nelson Mansoara (JURNAL LENTERA BISNIS, 2026)
Low work ethic and weak work discipline among civil servants in remote regional government offices often underlie fragile organizational commitment a problem that has received insufficient scholarly attention in Indonesian public sector HRM literature. This study examines the partial and simultaneous effects of work ethic and work discipline on employee organizational commitment at the Social Affairs Office of Pegunungan Arfak Regency. Grounded in Allen and Meyer's (1990) three-component commitment model, Weber's (1958) work ethic theory, and Skinner's (1938) reinforcement theory, this research employs a quantitative census approach involving all 54 active employees. Data were collected via Likert-scale questionnaires and analyzed with multiple linear regression using IBM SPSS. Results show that: (1) work ethic has a positive and significant effect on organizational commitment (β=0.412, t=4.183, sig=0.000), (2) work discipline has a positive and significant effect on organizational commitment (β=0.501, t=5.087, sig=0.000), (3) simultaneously both variables are significant (F=37.214, sig=0.000) with R²=0.601, meaning 60.1% of variation in organizational commitment is explained by these variables. Work discipline proves to be the more dominant predictor. These findings contribute theoretically to extending organizational commitment models within remote regional government contexts, while offering practical implications for HRM policy in Pegunungan Arfak Regency.